Pausing and Starting in The Holy Quran: A Phonetic, Syntactic, and Semantic Study - Azouzi, Sanae (Insyirah: Jurnal Ilmu Bahasa Arab dan Studi Islam, 2024)
This paper aims to demonstrate the integrative relationship between the science of stopping and starting in the Holy Quran, and the levels of linguistic study (phonetic, phonological, morphological, syntactic, semantic, and pragmatic). We chose to study the relationship between; the phonetic component, through some phonetic phenomena generated by stopping and starting, such as inclination, vibration, deletion, and addition, and the syntactic component that deals with the distribution and arrangement of words in sentences. Also, the relationship that connects them to give them semantic significance considering the representational relationships between words. We demonstrated this through an applied phonetic, syntactic, and semantic study in some Quranic verses to show the impact of stopping and starting in integrating these levels. We concluded that it is necessary to go beyond the inherited view of separating the levels of the Arabic tongue, which has arisen through linguistic theories aimed at specialized scrutiny, thus narrowing the perspective and obscuring the comprehensive vision.